STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN SISWA DALAM MEMBACA DAN MENGHAFAL AL-QURAN DI SD SABBIHISMA PADANG SUMATRA BARAT - Raja Muhammad Kadri; Arwansyah Kirin (Universitas Muhammadiyah Surakarta, 2022)
Al-Qur’an education is currently not only limited to houses and places of worship, but has begun to enter into school activities. One of the educational institutions that organizes Qur’anic education in schools is Sabbihisma College. Sabbihisma College has been around for a long time and organizes Al-Qur’an education and has graduates many students who are able to read and memorize the Qur’an with a target of one juz. This research took place in one of the branches of the Sabbihisma College, namely SD Sabbihisma. This study aims at: 1) finding out the strategies of teachers in increasing ability students’ in reading and Qur’an at SD Sabbihisma. To achieve the objectives, a qualitative approach was used with the type of research “field research.” Research informants are school foundation administrators, school principals, coordinators of the tadarus and tahfiz al-Qur'an fields and al-Qur'an teachers.The results of this study reveal that there are several teacher strategies in an effort to improve students ability to read and memorize the Qur’an, namely. First, maximing Al-Qur’an learning in the classroom by presenting two Quranic teachers. Second, using a limit card as a limit control for reading tadarus and tahfiz Al-Qur’an. third, form a “clinic” for improving reading and memorizing the Qur’an which is held one a week. Fourth, read and repeat rote every morning before starting the lesson.